(untitled) (Scientific journal of the Fergana State University, 2024)
The article is dedicated to the memory of the excellent researcher of the honey plants of Central Asia Gulyam Khamidovich Khamidov. Professor Gulom Khamidovich first worked as a laboratory assistant, junior researcher, and head of the laboratory at the Institute of Botany of the Academy of Sciences of Uzbekistan, and from 1991 until the end of his life, he worked as a professor and head of the department at Fergana State University.